Evaluation of the Clinical Effectiveness of the Drug Laennec in Complex Rehabilitation of Patients with Post-COVID Syndrome: a Randomized Trial - Olga V. Yurova; Tatiana V. Konchugova; Tatiana V. Apkhanova; Ilmira R. Gilmutdinova; Valeriia A. Vasileva; Detelina B. Kulchitskaya; Larisa A. Marchenkova; Oleg S. Glazachev; Elena N. Dudnik; Maryana A. Ansokova (Вестник восстановительной медицины)
INTRODUCTION. The development of post-COVID syndrome is accompanied by an increase in markers of systemic inflammation, a violation of the detoxification function of the liver, caused by both direct viral damage to hepatocytes and an increased iatrogenic load on the hepatobiliary system due to polypharmacy.